Start with why : how great leaders inspire everyone to take action - Sinek, Simon (New York, NY : Portfolio / Penguin, 2025)
"Start With Why shows that the leaders who've had the greatest influence in the world all think, act, and communicate the same way-- and it's the opposite of what everyone else does. People like Martin Luther King Jr., Steve Jobs, and the Wright Brothers had little in common but they inspired people, not with WHAT they did...but with WHY they did it. Sinek provides a new, easy to understand, framework that inspires people to build organizations and lead movements in a more powerful and effective way. And it all starts with WHY."-- jacket flap.
First published in hardcover as Start with why by Portfolio / Penguin in 2009.
Includes bibliographical references (pages 231-241) and index.
Keywords: Leadership